Pembuatan Program Aplikasi Perhitungan Nilai Rapot pada SMK Permata Indah - Erlina Octavia (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The calculation of the value of report cards in SMK Permata Indah still using manual way. The calculations are done one by one by subject teachers. Making a report card that is currently done can lead to miscalculation of the value of report cards. To reduce the risk of error then created a web-based account rate calculation application